Empowering Baturiti MSMEs through Website Integration and Social Media Marketing Strategies - Wicaksana, GDA; Cahyono, Irfan; Sudrajat, Kadek; Suprihatin, Yeni (Room of Civil Society Development, 2025)
Digital transformation plays a critical role in supporting the sustainability and competitiveness of local enterprises in rural and tourism-based regions. This study explores the development of a digital platform designed to enhance the marketing capacity of Micro, Small, and Medium Enterprises (MSMEs) in Baturiti Village, Bali. In response to limited digital visibility and market access among local entrepreneurs, a website was created to serve as a centralized platform that integrates business profiles, product galleries, WhatsApp communication, and Google Maps navigation. Using a descriptive qualitative approach, the research involved five selected MSMEs representing various sectors such as traditional food, retail, and crafts. The findings indicate that the platform effectively supported MSME digitalization through three core strategies: digital marketing integration, product quality presentation, and product diversification. The website not only increased visibility and customer engagement but also fostered community-based empowerment and collaboration. This model offers practical insights into how localized digital tools can bridge the digital divide and support inclusive economic development in rural tourism areas.